Analysis of zero waste management and occupational health and safety using Fine-Kinney and analytical hierarchy process - Apaydin, O.; Karan, T. Y. (SPRINGER, 2025)
This study was conducted on the five considered campuses of a university in Istanbul and focused on monitoring the waste management system within the scope of occupational health safety (OHS) and minimizing the possible risks that may arise, specifically within the zero waste management (ZWM) system. The observation/monitoring/correction studies within the scope of OHS on the campuses were conducted under nine main criteria. A checklist was used qualitatively, the Fine-Kinney method and analytic hierarchy process (AHP) were used quantitatively to plan and evaluate any risks at the campuses. In the evaluation conducted according to nine criteria for the campuses using the Fine-Kinney method, risk scores were calculated for campuses before and after the training given to the relevant personnel on OHS and ZWM. According to the results obtained; while the risk scores before the training varied between 63 and 900, it was determined that they varied between 15 and 60 after the training. The significant improvement in the obtained risk scores reveals the necessity of periodic training activities. In addition, in the prioritization studies conducted using the AHP, it was calculated that the safety precaution weights varied between 0.070 and 0.764, while the accident severity weights varied between 0.064 and 0.541. Accordingly, it was concluded that the models created in this study can be used as useful models for future projections in studies to be conducted on the subject, depending on both the level of safety measures and the severity of accidents.
Keywords: Accident severity; Analytic hierarchy process; Occupational health safety; Safety precaution; Zero waste management; HIMACHAL-PRADESH; CONSEQUENCES; Environmental Sciences & Ecology